Determination of Hydrological Niche of Restionaceae Species in Silvermine, South Africa - (:unkn) unknown (My University, 2021)
The Restionaceae species of the Fynbos biome is part of the Cape Floristic Region (CFR), one of only six floristic kingdoms in the world. It is threatened by urbanization, agricultural expansion and groundwater extraction. Therefore, it is necessary to assess and monitor the Restionaceae species. South Africa is a semi-arid environment, and hydrological factors are the main variables in the determination of species niches. This study investigates the microclimate at Silvermine, and examines the contribution of hydrological variables to plant species distribution, thus creating a hydrological niche. This study generates its own unique microclimate hydrological datasets for modelling species niche. Additionally, this study assessed and modelled the effectiveness of the use of hydrological variables to determine species hydrological niche, at a microclimate level in a semi-arid environment. It also provided evidence regarding the importance of the study to conservation and future climate change impact analysis of plant species and species richness. As the CFR has been widely used as a test case for modelling climate change impacts on biodiversity at biome and species level, many studies have projected range contractions and species losses. This study should be further explored as representative of species interaction with the hydrological niche of the Restionaceae species in the long term observations.
Keywords: African Research